From Patterns to Discoveries - Berthold, Michael R. (My University, 2012)
Data mining started off by finding clearly defined patterns in large sets of relatively homogeneous data. Over the years, increasingly complex data sources were tackled. As a result, newly developed methods grew in complexity, but the basic assumption that the type of pattern sought for was known beforehand remained a constant. I argue that we will ultimately require new systems which enable users to gain new, often surprising insights before they can even determine how to fine-tune and/or validate the patterns themselves.
Keywords: 004